Manufacturing network simulation using a data–driven model. (9th January 2012) - Essaid, Mohand; Fré,; dé,
The globalisation of markets and worldwide competition forces manufacturing enterprises to enter into alliances, leading to the creation of distributed manufacturing enterprises. Before forming a partnership, it is essential to evaluate the viability of a proposed manufacturing network. This paper presents a generic simulation model that attempts to create reusable enterprises modules for evaluating supply–chain performance. The simulation is developed using ARENA software coupled with a spreadsheet configuration tool. The latter constitute a manufacturing library from which various configurations of supply chain can be implemented and simulated.